Sustainable FDI for sustainable development - Karl P. Sauvant; Howard Mann (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Based on an examination of 150 instruments (ranging from international investment agreements to MNE codes) that deal with the interaction between host countries and MNEs, this Perspective identifies common FDI sustainability characteristics and suggests ways in which stakeholders can utilize and promote them, including in the context of investment facilitation.
Keywords: 330